ESPECTROS REMEMORADOS: as representações da morte em Largo do Desterro, de Josué Montello - ROCHA, Aline Ferreira (2024)
The present study, within the scope of Maranhão literature, focuses mainly on the novel Largo do Desterro (1981), by Josué Montello, and aims to investigate the representation of death and its various nuances. From the protagonist, Major Taborda is constantly confronted with finitudes throughout his life. Along this path, life and death clash, and with this, we seek to translate the meaning in the relationship between death and being throughout history and, consequently, in literature. Based on the reflections surrounding this novel, we observe that death is a common element among all the characters. Initially, a historical and philosophical approach to the theme of death and its expansion into the literary field was carried out, to understand the relevance of this work in the list of Brazilian literature. A correlation was also presented between the conceptions of death and memory, which can be contemplated in the Montellian narrative, based on theoretical studies of works chosen in order to support this entire analysis, with the theoretical framework composed of scholars of historical and philosophical theories, and the field of literary criticism respectively, such as Ariès (2000, 2012), Barbagli (2015), Bosi (2006, 2015), Candido (2000, 2006a), Oliveira (2017), Ricoeur (1994, 1995, 2007), Schopenhauer (2000, 2005) and among others.